A Market Entry Timing Model for New Technologies - Kalish, Shlomo; Lilien, Gary L. (Management Science, 1986)
A central issue in new product development and planning is the market timing/entry decision. An entry too early may risk pushing an under-developed product into the marketplace, with possible negative results; however, a product/technology may sacrifice sales if entry is delayed too long. A market diffusion model is developed that incorporates negative word-of-mouth associated with new product failure, resulting from premature introduction. Our analysis suggests that, when introducing a new technology, significant penalties may be associated with mistiming introduction. The analysis was applied to a problem facing the photovoltaic program of the Department of Energy. A proposal to construct a 100-home demonstration program for photovoltaics (PV) in the Southwest was being evaluated. The analysis of this case showed that an argument can be made to delay the demonstration program for several years and that significant risks (in terms of lowered ultimate market penetration) exist when starting this PV demonstration program prematurely.